RETRACTED: Differential Regulation of the EGFR/PI3K/AKT/PTEN Pathway between Low- and High-Grade Gliomas - Alveiro Erira; Fernando Velandia; José Penagos; Camilo Zubieta; Gonzalo Arboleda (Brain Sciences)
Gliomas represent 70% of all central system nervous tumors and are classified according to the degree of malignancy as low- or high-grade. The permanent activation of the EGFR/PI3K/AKT pathway by various genetic or post-translational alterations of EGFR, PI3KCA, and PTEN has been associated with increased proliferation and resistance to apoptosis. The present study aimed to analyze the molecular/genetic changes in the EGFR/PI3K/AKT/PTEN pathway between low-grade and high-grade gliomas in a sample of Colombian patients. A total of 30 samples were tested for PI3K and PTEN mutations, EGFR, PI3K, and AKT gene amplification, AKT, PI3K, BAX, Bcl2 expression levels, and phosphorylation of AKT and PTEN, EGFR and/or PI3K gene amplification was found in 50% of low-grade and 45% of high-grade ones. AKT amplification was found in 25% of the low-grade and 13.6% of the high-grade. The expression of PI3K, AKT, Bcl2, and BAX was increased particularly to a high degree. AKT phosphorylation was found in 66% of low-grade and 31.8% of high-grade. Increased phosphorylation of PTEN was found in 77% low-grade and 66% high-grade. Our results indicate that alterations in the EGFR/PI3K/AKT/PTEN pathway could be important in the initiation and malignant progression of this type of tumor.